Development of arteriovenous anastomoses in the skins of rats during the fetal period - í‡imen, Mehmet (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In order to describe the development of AVAs in Rattus norvegicus species, the fetus were followed up for 10 days after coitum. The serial sections obtained from the fetuses of 10-20-day rats were subjected for examination under the light microscope. Various staining processes were applied on the preparations and the simple types of AVAs determined in the skin of fetuses were observed until birth every day. The regions with AVAs were then photographed by photomicroscopy and evaluated. An increase in the smooth muscles in the wall structure of simple anastomoses was observed in 10-day embryos until birth.